Isolation and characterisation of autochthonous Saccharomyces cerevisiae from 'Pago' Merlot wines of Utiel‐Requena (Spain) origin. (28th November 2021) - Ut, C.; Berbegal, C.; Lizama, V.; Polo, L.; García, M.J.; Andrés, L.; Pardo, I.; Álvarez, I.
Abstract: Background and Aims: To achieve both the control of the undesirable yeasts and the improvement of the characteristics of Merlot 'Pago' wines, Saccharomyces cerevisiae yeast diversity was investigated in a spontaneous 'Pago' Merlot fermentation from the Utiel‐Requena region (Spain). Isolates of S. cerevisiae were characterised by a holistic procedure using the same Merlot grape must from which they were isolated. Methods and Results: Yeasts were identified by internal transcribed spacer analysis and typed by Hinf I mDNA restriction analysis. Growth and metabolic characteristics of the isolates were determined by laboratory‐scale (50 L) fermentations of Merlot must and the composition of the polyphenolic and the volatile compounds and the sensory attributes of the wines were determined. Twelve S. cerevisiae strains were isolated and characterised. Strains 2E, 4A, 7A and 7F had better growth characteristics. Strains 9C and 7F produced wines of good intensity and colour quality, marked intensity and aroma quality, fruity character and better overall quality. Strain 9C displayed poor growth. Conclusions: Strain 7F combined good growth characteristics and produced Merlot wines with the best colour, aroma and flavour characteristics during microvinifications. Significance of the Study: Characterisation of S. cerevisiae made entirely in Merlot grape must allowed the influence of yeast strains on the final characteristics of commercial‐scale Merlot 'Pago' wines to be more accurately deduced.